The black associativism in Rio Claro: subjects, practices and ideas in the republic - Picelli, Pedro de Castro (Laboratório Editorial Faculdade de Ciências e Letras, 2019)
The associativism in Rio Claro was "founded" in the late nineteenth century and has the last date of organization in 1951. Thus, the structural historical period of club formation can be read as a long process begun even in the slave period and which points in the second half of the twentieth century to the existence, not necessarily simultaneous in time, of more than a dozen of them. The associatives experiences of social space present themselves as an important key to thinking about the transformation of social relations after 1888. Thus, we will seek in this brief article to present some of the black clubs, members and practices to reflect the implications of the experiences of these associations for repositioning of the subjects and social relations in the social space rio-clarense.